Molecular model and analysis of glass transition temperatures for polymer-diluent-salt systems - Kim, JY; Hong, SU; Won, J; Kang, YS (AMER CHEMICAL SOC, 2000)
Three explicit mathematical models have been developed to predict glass transition temperatures of binary polymery-diluent and polymer-salt systems as well as ternary polymer-diluent-salt systems based on the configurational entropy model and the Flory-Huggins theory. In the presence of salt, the specific ionic interactions of polymer and/or diluent with salts have been taken into account. The validity of the mathematical models mere examined against the experimental glass transition temperatures of poly(2-ethyl-2-oxazoline)-propylene carbonate, poly(2-ethyl-2-oxazoline)-silver triflate, and poly(propylene oxide)-lithium iodide as well as poly(2-ethyl-2-oxazoline)-propylene carbonate -silver triflate. The models adequately predict glass transition temperatures depending on the concentrations of the diluent as well as the salt in both binary and ternary systems.
Keywords: STATISTICAL THERMODYNAMICS; ELECTROLYTES; BEHAVIOR